METHODOLOGICAL BASIS FOR CREATING AN ELECTRONIC APPLICATION TO THE TEXTBOOK "PHYSICS 9" - Blagodarenko Л.Ю. (Journal of Information Technologies in Education (ITE), 2010)
The results of the analysis of educational software that exist on the Ukrainian market are presented. The structure, functions and advantages of the electronic application to the textbook "Physics 9" are defined.